2020
DOI: 10.1111/acps.13179
|View full text |Cite
|
Sign up to set email alerts
|

Evening chronotype, disordered eating behavior, and poor dietary habits in bipolar disorder

Abstract: Evening chronotype, disordered eating behavior, and poor dietary habits in bipolar disorder. Objective: Our aim was to evaluate the relationship between evening chronotype, a proxy marker of circadian system dysfunction, and disordered eating behavior and poor dietary habits in individuals with bipolar disorder (BD). Methods: In this cross-sectional study, we evaluated 783 adults with BD. Chronotype was determined using item 5 from the reduced Morningness-Eveningness Questionnaire. The Eating Disorder Diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 76 publications
(92 reference statements)
1
28
0
Order By: Relevance
“…We strongly support the suggestion made by Romo‐Nava and colleagues to study chronotherapeutic interventions 1 for disordered eating behavior in BD, and we think that although limitations of the evidence base must be considered, light therapy has a favorable efficacy and safety profile as a treatment option in bipolar depression. It is an interesting candidate to be studied in conjunction with psychoeducation on sleep hygiene and healthy eating behavior in evening chronotype individuals with BD and disordered eating.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…We strongly support the suggestion made by Romo‐Nava and colleagues to study chronotherapeutic interventions 1 for disordered eating behavior in BD, and we think that although limitations of the evidence base must be considered, light therapy has a favorable efficacy and safety profile as a treatment option in bipolar depression. It is an interesting candidate to be studied in conjunction with psychoeducation on sleep hygiene and healthy eating behavior in evening chronotype individuals with BD and disordered eating.…”
supporting
confidence: 77%
“…1 Morning light therapy advances circadian phase measured by salivary dim light melatonin onset and may be an interesting therapeutic option to be studied. 1,2 Furthermore, a systematic review has concluded that bright light therapy may be effective for disordered eating behavior. 3 Light therapy has not much been studied in bipolar disorder, but recently five randomized, placebo-controlled trials (RCT) have been published, 4 supporting efficacy for light therapy in bipolar depression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, efficient therapeutic strategies are needed to limit the progression of weight gain. Multifactorial approaches have been proposed, based mainly on dietetic and behavioral changes [2], while pharmacotherapy for obesity or binge eating disorder remains of limited efficacy and poor tolerance for most drugs [3,4]. Over the last decade, intensive effort in gut microbiota's Nutrients 2021, 13,1902 2 of 14 research allowed to elucidate distinct bacterial signaling pathways related to host energy harvesting, fat deposition, inflammation and insulin resistance in obesity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Mood states and mood symptom burden may explain in part these inconsistencies. In addition, evening chronotype may be associated with significantly higher rates of both binge eating and unhealthy eating habits 87 …”
Section: Lifestyle Mediatorsmentioning
confidence: 99%